Síntese de clorinas anfifílicas com potenciais aplicações em terapia fotodinâmica - Santos, Fabiane Aparecida Batalha dos (Universidade Federal de São Carlos, 2012)
The main objective of this work was to construct amphiphilic chlorins with low aggregation in a physiological environment. The synthesis and structural characterization of the target compounds were carried out, and preliminary photophysical studies have been performed to point out the best candidates for further photochemical and biological studies (PDT studies) Initially, the porphyrin precursor 2 was synthesized using accessible reagents and a simple methodology, as described in Scheme 3. Scheme 3. Synthesis of new chlorins. i) C6H5Cl/PTSA, reflux, 2h and then ii) MeOH/H2SO4 5%, rt, overnight, 72% yield (2 steps); iii) solvent/conditions (Tabela 1) and maleiimide 9; iv) solvent/conditions (Tabela 2) and maleiimide 10; v) NH2OCH2CH2OH, THF, reflux. The second part of the work involved the Diels Alder reactions between the dienophiles (9 and 10) and porphyrin 2, as shown in Scheme 3. The synthesis of the dienophiles involved initial protection with ethylene glycol (to 7) or ethylenedithiol (to 11). The ethylene glycol protected compound 7 did not provide the expected results yielding only by-products. On the other hand, the approach using ethylenedithiol as protecting group allowed the effective synthesis of maleimides 9 and 10 (Scheme 4). Scheme 4. Synthesis of maleimides. We decided to study the relative reactivity of maleimides 9 and 10 under the Diels-Alder reactions conditions with porphyrin 2, as well as establish the ideal conditions to obtain chlorins 3a/3b and 4a/4b. Our best results were obtained for chlorins 3a and 3b with 37% and 37% yield for both; for chlorins 4a and 4b the yields were 36% and 35%, respectively. Finally, the versatility of chlorins 4a and 4b, as multi-functionalizable photosensitizers, was evaluated. These compounds reacted with 2-aminoxyethanol and the oxime-type amphiphilic derivatives 5a/5b were obtained in 67% and 74% yield, respectively. The reported compounds in this dissertation were characterized by 1D and 2D NMR spectroscopy, UV-Vis spectroscopy, infrared spectroscopy and low or high resolution mass spectrometry. The structures were assigned unambiguously. Through the synthetic studies, some photophysical tests, such as singlet oxygen production measurements, were conducted in order to evaluate the potential of chlorins 3a/3b and 4a/4b for PDT studies. 1H NMR aggregation studies were also performed to demonstrate the absence of aggregation in solution at the studied concentrations (high concentrations).
Synthesis of amphiphilic chlorins with potential applications in photodynamic therapy
Keywords: Química orgânica; Diels-Alder; Síntese orgânica; Terapia fotodinâmica; Anfifílico; Protoporfirina; CIENCIAS EXATAS E DA TERRA::QUIMICA